Perceptions of Nursing and Physical Therapy Students Toward Peer-Led Interprofessional Education in Manual Handling - McCrorie, P.; Roberts, Pamela; Sainsbury, David; Boldy, Duncan; Gower, Shelley (2016)
Perceptions of first-semester BSN students (N = 220) who received education on patient moving and handling skills from either fourth-year physical therapy/physiotherapy student peer teachers (n = 8) or regular nurse educators were obtained via validated scales and focus groups. There was a significant increase in the mean scores of items concerning communication skills in both groups, with increased scores for all items in the peer-led group. The teaching skills of physical therapy/physiotherapy student peers were evaluated highly by the nursing students.